2015
DOI: 10.3945/ajcn.114.104646
|View full text |Cite
|
Sign up to set email alerts
|

Flavanones protect from arterial stiffness in postmenopausal women consuming grapefruit juice for 6 mo: a randomized, controlled, crossover trial

Abstract: Background: The consumption of citrus fruits is associated with health benefits. However, clinical data regarding the effects of grapefruit flavanone consumption on vascular function are lacking. Objective: The objective of the present study was to address the role of flavanones in the long-term effects induced by grapefruit juice (GFJ) consumption on vascular function in healthy postmenopausal women. Design: Forty-eight healthy postmenopausal women aged 50-65 y within 3-10 y since menopause, a body mass index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 41 publications
2
61
1
1
Order By: Relevance
“…To our knowledge, only a handful of placebo-controlled trials with flavanones have been conducted to date. The first long-term trial, a 6-mo flavanone intervention trial with grapefruit juice (containing 210 mg naringenin glycosides/d) in healthy postmenopausal women improved arterial stiffness (19). In another 2-mo intervention with flavanone-rich orange juice, global cognitive function was improved (55), which is consistent with effects previously observed in animal models (44).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only a handful of placebo-controlled trials with flavanones have been conducted to date. The first long-term trial, a 6-mo flavanone intervention trial with grapefruit juice (containing 210 mg naringenin glycosides/d) in healthy postmenopausal women improved arterial stiffness (19). In another 2-mo intervention with flavanone-rich orange juice, global cognitive function was improved (55), which is consistent with effects previously observed in animal models (44).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies were conducted to assess the effects of clear apple juice, cloudy apple juices, squeezed orange juice, and grapefruit juice on blood pressure in healthy adults or adults with hypercholesterolemia and hypertriglyceridemia. No effect of any of these interventions was found on SBP or DBP [53,54,55]. In addition, two studies assessing the effects of vegetable juice showed that either beetroot juice or low sodium vegetable juice could not decrease blood pressure in individuals with type 2 diabetes or in people with metabolic syndrome [60,63].…”
Section: Juices and Blood Lipidsmentioning
confidence: 99%
“…No significant differences were found in plasma total antioxidant capacity, antioxidant vitamins, LDL oxidation, or erythrocyte antioxidant enzyme activity [83]. In another study [53], the antioxidant effect of grapefruit was investigated, but results showed that oxidative stress was not affected after consumption of grapefruit juice.…”
Section: Mechanisms Of Action Of Juice On Cardiovascular Diseasesmentioning
confidence: 99%
See 2 more Smart Citations